2020
DOI: 10.1111/jpc.14921
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cows milk‐related symptom scoring awareness tool in young Turkish children

Abstract: Background: The diagnosis of cows milk protein allergy (CMPA) is not always easy. Cow's Milk-related Symptom Score (CoMiSS) has been developed to raise the awareness of CMPA among the primary health-care providers. In this study, we aimed to evaluate the validity of CoMiSS as a diagnostic approach of CMPA in infants in our country. Methods: Infants with a CoMiSS of more than 12 points were included. An elimination diet was implemented in these infants for 4 weeks, and CoMiSS was reapplied. Infants with a reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 19 publications
0
32
1
Order By: Relevance
“…The study also showed that some symptoms, such as skin involvement, were more frequently observed in children with confirmed allergy whose score was significantly higher. The authors therefore concluded that the systematic evaluation of symptoms associated with CoMiSS can aid the selection of infants who might benefit from an elimination diet [147,148].…”
Section: Accuracy Of Clinical Score Compared To Ofcmentioning
confidence: 99%
“…The study also showed that some symptoms, such as skin involvement, were more frequently observed in children with confirmed allergy whose score was significantly higher. The authors therefore concluded that the systematic evaluation of symptoms associated with CoMiSS can aid the selection of infants who might benefit from an elimination diet [147,148].…”
Section: Accuracy Of Clinical Score Compared To Ofcmentioning
confidence: 99%
“…Four studies scored high risk in the patient selection domain: two used a case‐control study design, 16,21 and two selected only infants that scored a CoMiSS™ of >12 22,23 . Four studies scored high risk for index test interpretation bias, due to the lack of pre‐specified threshold criterion for a positive screen and a lack of blinding to the results of the reference standard 16,22–24 . All studies scored high risk of bias for not using DBPCFC as the reference standard 16,21–26 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the reported accuracy estimates are likely to overestimate the real performance of the score, first because response to elimination diet was defined as a decrease in the CoMiSS™ score (incorporation bias) and the cut‐off of 9 was based on ROC analysis. Selbuz evaluated CoMiSS™ against OFC in infants 0–12 months with an initial CoMiSS™ ≥12 22 . Reported sensitivity and specificity estimates based on ROC analysis have not been included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations